Australia-China-Africa investment partnerships: A new frontier for triangular cooperation?. Issue 1 (7th March 2016) - de Jonge, Alice
Abstract : Purpose: – This paper aims to examine the potential for "triangular cooperation" between investment partners from Australia, China and host African nations to contribute to the economic development in Africa. Design/methodology/approach: – The paper discusses a number of complementarities between Australian and Chinese investors in mining, agriculture, energy, research and education and finance – sectors vital to Africa's future development. These complementarities are examined in light of recent development studies on the benefits of triangular cooperation and recent literature examining links between foreign direct investment (FDI) policy and economic development. Findings: – The paper concludes that there is much to be gained by making the most of the existing and potential synergies between Australian, Chinese and local investors in African settings. Research limitations/implications: – The implications of this paper are, first, that African nations should keep the benefits of triangular cooperation in mind when designing FDI policies and, second, that Australian and Chinese investors should be more willing to explore potential investment partner synergies when investing in Africa. The paper also suggests an agenda for future research into how good design of FDI policies might best promote healthy economic development in African nations. Practical implications: – Australian and Chinese companies should be more willing to explore potential avenues for cooperation when investing in Africa, while African governments should be more mindful of how rules and policies can maximise the local benefits of FDI. Social implications: – African governments should be more mindful of the quality, rather than the quantity of FDI when drafting relevant laws and policies. Originality/value: – The value of the paper is in applying the concept of "triangular cooperation" to direct investment. The paper also provides an original focus on Australia-China investment synergies in African settings.